The Difference on Pain and Range of Motion After High-Intensity Laser Therapy on Myositis Ossificans of the Right Deltoid Muscle: A Case Report - Dian Herdiansyah; Tertianto Prabowo; Rachmat Z. Goesasi (Indonesian Journal of Physical Medicine & Rehabilitation, 2017)
Background: Myositis Ossificans (MO) is a non-neoplastic proliferation of bone and cartilage tissue aftermicro-injuries on muscle, as a result of dysregulation response to inflammation on stem cells.Results: A patient, 50-years old man with pain and restricted movement of the right shoulder, that rose 8hours after exercise. The radiograph revealed the MO on the right Deltoid muscle. The patient has receivedthe high intensity of laser therapy for two continuous therapy. The result after therapy was decreased ofpain and can move the right shoulder easily. Furthermore, after two times/week for four weeks of therapy,there was no pain, as well as the x-ray was showed reduced the size of calcification.Conclusion, The high intensity of Laser therapy was improved the pain dan reduced the size of MO onright deltoid muscleKeywords: Myositis Ossificans, Deltoid Muscle, High Intensity of Laser Therapy